2018
DOI: 10.1007/s10072-018-3432-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Italian version of the Cognitive Reserve Scale (I-CRS)

Abstract: The original definition of cognitive reserve (CR) refers to the individual differences in cognitive performance after a brain damage or pathology. Several proxies were proposed to evaluate CR (education, occupational attainment, premorbid IQ, leisure activities). Recently, some scales were developed to measure CR taking into account several cognitively stimulating activities. The aim of this study is to adapt the Cognitive Reserve Scale (I-CRS) for the Italian population and to explore its psychometric propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 39 publications
4
24
0
Order By: Relevance
“…There was inconsistent evidence on the construct validity of the CRS in healthy participants when taking into account that the methodological quality was overall good, but about half of the studies could not find expected significant associations between cognitive outcomes and the CRS. Altieri et al [58] found weak positive associations between CRS scores and global cognitive functioning (MMSE, r = 0.26, p<0.001 and Montreal Cognitive Assessment, r = 0.28, p<0.001), long-term verbal memory (immediate recall Rey Auditory Verbal Learning Test (RAVLT), r = 0.25, p<0.001 and delayed recall RAVLT, r = 0.25, p<0.001) and visuo-spatial constructional abilities (Constructional Apraxia Test, r = 0.19, p<0.001). Cancino et al [59] found an association of the CRS with the Addenbrooke's Cognitive Examination-Revised (β = 0.223, p = 0.005).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was inconsistent evidence on the construct validity of the CRS in healthy participants when taking into account that the methodological quality was overall good, but about half of the studies could not find expected significant associations between cognitive outcomes and the CRS. Altieri et al [58] found weak positive associations between CRS scores and global cognitive functioning (MMSE, r = 0.26, p<0.001 and Montreal Cognitive Assessment, r = 0.28, p<0.001), long-term verbal memory (immediate recall Rey Auditory Verbal Learning Test (RAVLT), r = 0.25, p<0.001 and delayed recall RAVLT, r = 0.25, p<0.001) and visuo-spatial constructional abilities (Constructional Apraxia Test, r = 0.19, p<0.001). Cancino et al [59] found an association of the CRS with the Addenbrooke's Cognitive Examination-Revised (β = 0.223, p = 0.005).…”
Section: Resultsmentioning
confidence: 99%
“…In a further study by León et al [60], a correlation between the CRS and years of education (partial ŋ 2 = 0.07, p = 0.004) was found, but not with premorbid intelligence as measured with a Vocabulary subtest (r = 0.09, p = 0.33), nor occupation (F 2,116 = 0.11, p = 0.898). In the Italian version, Altieri et al [58] found associations between the CRS and years of education and occupation (r = 0.33 and ρ = 0.16, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations